THE STRUCTURE AND OPERATION OF THE TOURISM MANAGEMENT OF THE UNESCO WORLD HERITAGE TOKAJ WINE REGION IN HUNGARY, WITH A PARTICULAR FOCUS ON WINE AND HEALTH - Zoltán Szakál (PEOPLE: International Journal of Social Sciences, 2025)
The topics of wine and health are two disciplines that should be researched together and put in the focus of the given destination. The Hungarian Tokaj wine region has been a UNESCO World Heritage Site since 2002. The eponymous settlement Tokaj won the award for the best European tourist settlement and the wine region is a member of the European organization Viour. The destination has a development council, which also has a labor union. This team coordinates major investments in the wine region, including major tourism developments. At the municipality of Tokaj, tourism plays a prominent role, where there are tourism experts. In the city of Tokaj, there is a destination management organization and a tourinform, the task of which is to ensure the conditions for hosting tourists and to support tourists. He also has administrative, statistical and management tasks. The tourism operation of the area is a good practice and with the implementation of the "Essencia főtér" program, the city, the administrative center, enters a new dimension. Wine and health, wine culture, viticulture, winemaking and the attractions, restaurants, accommodation and infrastructure of the destination all operate in accordance with the principle of innovative new tourism. The new structure of tourism management is the focus of the research and the scientific article as well as the presentation, which includes both operative and strategic elements. The methodology is literature review and in-depth interview. In the case of the former, the author examines both domestic and international expertise and best practices.